Засади управління інформаційним забезпеченням комерціалізації інноваційної продукції підприємства - Ілляшенко, Сергій Миколайович; Шипуліна, Юлія Сергіївна (ВД "Гельветика", 2020)
У статті уточнено та систематизовано види інформації, які у сукупності складають систему інформаційного забезпечення управління комерціалізацією інноваційної продукції підприємств. Розроблено узагальнену схему взаємодії інформаційних потоків під час вирішення завдань комерціалізації. Систематизовано основні способи отримання й використання інформації, необхідної для розроблення та реалізації ефективних стратегій комерціалізації інновацій. Розроблено теоретико-методичний підхід до управління інформаційним забезпеченням комерціалізації інноваційної продукції підприємств. Отримані результати поглиблюють теорію інноваційного менеджменту підприємств щодо формування теоретико-методичних засад управління інформаційним забезпеченням процесу комерціалізації інновацій, що дає змогу підвищити ефективність відповідних управлінських рішень.

In the context of accelerating the pace of scientific and technological progress and the resulting changes in the vector of environmental factors, one of the most important competitive advantages of commodity producers is the effective system of commercialization of their innovative products. The loss of domestic producers in competition in many cases is caused by the low efficiency of commercialization strategies, even in the presence of modern high-quality products. Practice shows that developing effective strategies for the commercialization of innovative products requires adequate information support, which will ensure that management decisions are adequate to the market situation. Under these conditions it is actualized the problem of formation of information management system for commercialization of enterprise innovation. In the article, based on the analysis of literary sources and practice of innovative activity, types of information are specified and systematized. In the aggregate they form the information support system for managing the commercialization of innovative products of enterprises. A generalized scheme of interaction of information flows in solving problems of commercialization is developed. The main ways to obtain and use the information needed to develop and implement effective innovation commercialization strategies are systematized. The theoretical and methodical approach to the management of information support of commercialization of innovative products of enterprises is developed. The obtained results deepen the theory of innovative management of enterprises in the formation of theoretical and methodological foundations of information management of the process of commercialization of innovations. This improves the effectiveness of appropriate management decisions. Their practical implementation will allow increasing efficiency of innovative activity of domestic enterprises at the stage of commercialization of their innovative products. This will enhance their competitiveness in the domestic and international markets. Further research should be directed to the formation of a criteria base, a system of indicators, as well as formalized procedures for determining the necessary and sufficient level of information support for the organizational and economic mechanism for managing the commercialization of innovative products.
Principles for information support management of commercialization of innovative products
Keywords: інноваційний менеджмент; комерціалізація інноваційної продукції; інформаційне забезпечення комерціалізації; управління інформацією; підприємство-інноватор; innovation management; commercialization of innovative products; information support of commercialization; management of information; enterprise-innovator